Competência crítica em informação e fake news: das metodologias de fact-checking à auditabilidade do sujeito comum - Oliveira, Maria Lívia Pachêco de (2020)
The emerging occurrences in the informational panorama permeated by digital technologies challenge even the subjects considered competent in information. In view of this phenomenon, the possible relationship between critical information literacy and the disseminating practices of fake news is considered, taking as a reference for analysis the methodological strategies of information auditability adopted by fact-checking agencies. It starts with the hypothesis that the urgency of definitive answers about the veracity of certain information has progressively reduced the subject's critical state and stimulated the circulation of disinformation in the format of fake news. The general objective was to analyze the methodological information auditability strategies adopted by fact-checking agencies in the practice of disseminating fake news, taking as a theoretical reference critical information competence. In this perspective, it specifically aims to map the news checking methodologies adopted by fact-checking services; to characterize the strategies used by these services; to identify the recursive elements that validate the information created and conveyed through virtual communities; and, to establish, based on critical information literacy, determining elements for the treatment of information in cyberspace. The research has as theoretical references discussions about the truth, information literacy and critical information literacy, addressing the issues of autonomy and social protagonism as indispensable for facing the problems of disinformation, specified here in the fake news. It was decided to develop a theoretical-conceptual thinking about the main difficulties in auditing information in cyberspace. It is a basic strategic research, of an exploratory-descriptive level, with a qualitative approach, using the techniques of systematic observation and hermeneutical analysis based on content analysis. The universe consisted of the 65 fact-checking services signatory to the International Fact-Checking Network (IFCN) and the intentional sample was formed by 13 of these services. The collection and systematization of the data were carried out through information about the methodologies, publicly expressed by the fact-checking services and organized according to the categories formulated a priori. The analysis of the data took place around the identification of the existing elements in the fact-checking methodologies that reminds the forms of conception of competences in information, analyzing its characteris TIC in search of understanding the main elements used for the auditability of the information. The discussions enabled a conceptual deepening on the critical information literacy, and, with that, the results were reached pointed to the excess of evidence as a complicator of the auditability process, as well as the presence of a fundamental subjective component, the trust. The methodologies used in the fact- checking activity approximate more realistically to the performance of subjects in cyberspace, especially those who are not formally considered competent in information, that is, who have not undergone education or training that specifically contemplated the dimensions addressed by information literacy.